PENGEMBANGAN BERWIRAUSAHA BERBASIS DIGITAL DAN SELF LEADERSHIP - Runtu, Julius; Rahmawati, Veronika; Erwita, Monica Adjeng; Wulani, Fenika (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2023)
Entrepreneurship development needs to be pursued as early as possible since secondary education. Students who are a digital generation certainly need a positive distribution of digital skills that they generally have today. Digital-based entrepreneurship and self-leadership training is an alternative to helping students train their leadership through concrete activities which can at the same time help them channel their interests and prepare the mentality and skills needed at later stages of education. Student development programs in the form of entrepreneurship and character development programs have been successfully fulfilled in the service in the form of this training. This was proven based on the evaluation after the training which showed that the community service participants considered that the material provided was interesting and new. The resource persons were interactive and clear in providing material, as well as allocating training time that was appropriate to the situation and conditions of the trainees.